Subcellular distribution of enzyme I of the Escherichia coli phosphoenolpyruvate:glycose phosphotransferase system depends on growth conditions - Patel, Himatkumar V. (National Academy of Sciences, 2004)
The phosphoenolpyruvate:glycose phosphotransferase system (PTS) participates in important functions in the bacterial cell, including the phosphorylation/uptake of PTS sugars. Enzyme I (EI), the first protein of the PTS complex, accepts the phosphoryl group from phosphoenolpyruvate, which is then transferred through a chain of proteins to the sugar. In these studies, a mutant GFP, enhanced yellow fluorescent protein (YFP), was linked to the N terminus of EI, giving Y-EI. Y-EI was active both in vitro (≥90% compared with EI) and in vivo. Unexpectedly, the subcellular distribution of Y-EI varied significantly. Three types of fluorescence were observed: (i) diffuse (dispersed throughout the cell), (ii) punctate (concentrated in numerous discrete spots throughout the cell), and (iii) polar (at one or both ends of the cell). Cells from dense colonies grown on agar plates with LB broth or synthetic (Neidhardt) medium showed primarily bipolar or punctate fluorescence. In liquid culture, under carefully defined carbon-limiting growth conditions [ribose (non-PTS), mannitol (PTS sugar), or dl-lactate], cellular levels of enzymatically active Y-EI remain essentially constant for each carbon source, but fluorescence distribution depends on C source, cell density, growth phase, and apparently on “conditioned medium.” Fluorescence was diffuse during exponential growth on LB or ribose/Neidhardt medium. On ribose they became punctate in the stationary phase, reverting to diffuse when more ribose was added. In LB, both Y-EI and a nonphosphorylatable mutant, H189Q-Y-EI, showed a diffuse fluorescence during growth, but, shortly after the addition of isopropyl β-d-thiogalactopyranoside, Y-EI became bipolar; H189Q-Y-EI did not. The functions of EI sequestration remain to be determined.